Imaging the heat source of the Kangding high-temperature geothermal system on the Xianshuihe fault by magnetotelluric survey - Cheng, Yuanzhi; Pang, Zhonghe; Kong, Yanlong; Chen, Xiaobin; Wang, Guangjie (Geothermics, 2022)
•We have obtained a three-dimensional electrical model of the Kangding geothermal system.•The electrical model reveals the remarkable high conductivity anomalies beneath the Kangding geothermal field.•The conductors are explained as partial melt, which supply heat and fluids to the geothermal fields. The Kangding geothermal field along the Xianshuihe fault is a typical high-temperature geothermal system with an enormous capacity for geothermal power generation. The Xianshuihe fault is a major active sinistral strike-slip fault  in eastern Tibet Plateau, where the fault splits into three parallel branches near Kangding. We collected data from 17 magnetotelluric stations in the Kangding geothermal system. After data processing, the dimensionality of the subsurface structure was qualitatively estimated using the phase tensor. The electrical resistivity model inverted with ModEM shows the Kangding geothermal system from the surface to a depth of 20 km, which correlates closely with the near-surface geology. The synthetic tests confirmed that the main resistivity anomalies identified in the electrical resistivity model were robust. There are several significant low resistivity anomalies of less than 10 Ωm beneath the Kangding geothermal system. The cap rock and liquid-dominated reservoir can be interpreted as shallow conductive zones. The conductors beneath the Kangding geothermal field at a depth of 10 km are interpreted as an underlying zone of partial melt, which provides fluids and heat for the geothermal system. The partial melt fractions are in the range of 4–19%, confirming that there is a magmatic heat source beneath the Kangding geothermal system.